A research annual - Biddle, Jeff.; Emmett, Ross B. (Bingley, U.K. : Emerald, 2013)
Research in the History of Economic Thought and Methodology is an annual research series which presents materials in two fields, both broadly considered: the history of economic thought and the methodology of economics.The annual A-volume contains peer-reviewed articles comparable to other academic journals in the history of economics, except that long pieces are welcome. The A-volume also publishes symposia, and review essays on new works in the history of economic thought, methodology and related fields (philosophy of science, sociology of science, rhetoric of science, and intellectual history), including multiple reviews of the same work.The annual B- and C-volumes are archival supplements that present previously unpublished materials -- lecture notes, papers, longer manuscripts, correspondence, etc.- of interest in both fields addressed in the A-vol.
British economists on competition policy (1890-1920) / Nicola Giocoli -- Warren Samuels, the journal of economic issues / Malcolm Rutherford -- Warren J. Samuels : intellectual historian of economics / Ross B. Emmett -- A political philosopher's quick trip along the border between markets and ethics / Donald E. Frey -- A book that should not have been written / James S. Taylor -- Opening remarks : why "AAA economics" has legs / John D. Mueller -- Natural law economics : reading a theological economics / Joe Blosser -- Comments on redeeming economics / David M. Levy -- "Minding the gap" in economics : the contribution of redeeming economics / Edd Noell -- The economies of divine and human love / Jordan J. Ballor -- Notes on Mueller's redeeming economics / Dwight R. Lee -- Response : what exactly is "natural law economics"? / John D. Mueller -- Translating EmpireReinerts / Robert B. Ekelund -- American literature and the free market, 1945-2000Clunes / Sarah Skwire, Steven Horwitz -- Casualties of CreditWennerlinds / Richard Kleer -- Markets in the name of SocialismBockman's / Angus Burgin -- Building Chicago economics Van Horn, Mirowski, and Stapleford's / Stephen Martin.
Print version record
Keywords: Business & Economics -- Economic History; Business & Economics -- Economics -- Theory; Economic history; Economics; Economics -- History